PENELITIAN PENGARUH PEMANFAATAN KONSORSIUM MIKROBA PENITRIFIKASI DALAM BUDIDAYA UDANG - Komarawidjaja, Wage (Jurnal Teknologi Lingkungan, 2004)
Research on application of consortia of Nitrifying bacteria on shrimp culture wasconducted in Grinting, Brebes, Central Java . The experiment method usedconsortia of nitrifying bacteria as a sole treatment on Pond A and Pond B as acontrol. Intensive observation on some water qualities parameter such astemperature, salinity, pH and turbidity was conducted during shrimp culturalperiod. The research result is indicated by distinction of survival rate (SR)between Pond A and Pond B. The SR for Pond A is greater (32,5%) than inPon B (14%), but it is still low SR for aquaculture activity.